1992
DOI: 10.1093/clinids/14.1.272
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Fluoroquinolones with Other Drugs: Mechanisms, Variability, Clinical Significance, and Management

Abstract: Several important interactions of fluoroquinolones with other drugs have been reported in the literature. The absorption of all fluoroquinolones is almost entirely inhibited by concomitant administration of di- and trivalent cations, such as aluminum and magnesium contained in antacids. The inhibition of absorption can be significant and can potentially lead to the failure of treatment, even when fluoroquinolone doses are separated from antacid doses by hours. Certain isozymes of the cytochrome P-450 system ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 67 publications
0
41
0
1
Order By: Relevance
“…It is known that a mixture of NOR and Caffeine (CAF, Fig.1b) given simultaneously exhibits biological synergism in vivo [2,10]. It has been recently shown that CAF, a purine derivative, effectively forms hetero-complexes with a number of aromatic DNA intercalators, which may account for the observed changes of biological activity of these drugs in the presence of Caffeine, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that a mixture of NOR and Caffeine (CAF, Fig.1b) given simultaneously exhibits biological synergism in vivo [2,10]. It has been recently shown that CAF, a purine derivative, effectively forms hetero-complexes with a number of aromatic DNA intercalators, which may account for the observed changes of biological activity of these drugs in the presence of Caffeine, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one might expect that the observed biological synergism of NOR and CAF [2,10] may be due to the hetero-association of NOR with CAF and/or competition of NOR and CAF for DNA binding sites. In order to gain insight into the molecular action of the antibiotic Norfloxacin, the solution behaviour of NOR in the presence of CAF and DNA needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Feeds and water were withdrawn 8 and 2-hours respectively before drug administration. This was to reduce absorption variability due to drug-feed interaction and over dilution of the drug respectively (Randandt et al, 1992). Animals in each group were weighed individually and their dosages calculated based on weights (20 mg/kg b.w).…”
Section: Experimental Designmentioning
confidence: 99%
“…Caffeine can effectively form hetero association with many aromatic DNA intercalators that can change the biological activities of these drugs or make a computation with these aromatic drugs for the binding sites on DNA (Larsen et al, 1996;Traganos et al, 1991). Thus, as the norfloxacin molecules contain two fused aromatic rings just like caffeine, it can form interaction with caffeine (Radandt et al, 1992). This interaction may alter the pharmacokinetics or change the toxicity risk of the drugs (Radandt et al, 1992;Healy et al, 1989).…”
Section: Introductionmentioning
confidence: 99%